Evaluation of different solvents combined with the high pressure technique for extraction of total phenolic compounds and antioxidant activity of yerba mate (ilex paraguariensis) (Research, Society and Development, 2022)
It is increasingly common to use plants or derivatives to reformulate, replace or create food products, with the aim of adding nutritional values and satisfying the consumer who is increasingly demanding healthier foods. Yerba mate (Ilex paraguariensis) leaves are known for their antioxidant and antimicrobial potential, as well as improving glucose tolerance and anti-inflammatory effects. The objective was to analyze different solvents with the high pressure technique in order to obtain yerba mate extracts with a greater amount of total phenolic compounds and antioxidant activity. Ten treatments were performed, five subjected to high pressure extraction (150 MPa / 30 minutes) using as solvents: ethanol, H2O with ethanol, methanol, glycerin and lactic acid, and five not subjected to the technique. Regarding the solvent, the best results were for H2O + glycerin (50%). It was also observed that the highest content of phenolic compounds was in the extraction of yerba mate with pressure of 600.42 mg EAG/L, the same occurred with the antioxidant activity, and in the ABTS method the value was 619.70 TEAC /g without pressure and was increased to 702.53 TEAC/g with the use of the technique, for DPPH comparing before 954.37 IC50 (mg/mL) and after high pressure 1044.96 IC50 (mg/mL). It is concluded that high pressure extraction was essential to assist in the extraction of greater amounts of antioxidants using a biodegradable solvent.